Saneamento básico e a qualidade microbiológica da água no auxílio à segurança hídrica em áreas rurais - Dias, Fernanda Azevedo [UNESP] (My University, 2021)
In Brazil, water resources reach 12% of the total fresh water in the world, which means an abundance of this resource considering only the volume. Even though it is abundant, the distribution is uneven in a country of continental dimension, where there is a large population, there is little water and where there is a low population index, a large availability of water, although quantity is not synonymous with quality. In the rural environment, the main source for obtaining water is through wells, the vast majority of which are not granted, therefore, there is no knowledge of the status of these waters in terms of their quality, aiming at different uses, in addition to the difficulties that exist in urban areas. The lack of access to the source of drinking water is still a situation present in the Brazilian social reality, and particularly critical for part of the rural population, who live in a situation of vulnerability in the area, due to social differences and the attention of the State through of public policies. The lack of inspection, lack of management support and very low coverage of water supply in rural environments thus leads to a lack of water security, directly impacting the quality of life and well-being of the population, in addition to the high spread of diseases. The region of Ilha Solteira (SP) has an extensive rural area, in some areas, despite the proximity to the urban area, there is a lack of basic sanitation and there is no distribution of treated water to families, which use water from well stored in water tanks, without proper treatment for consumption. The objective of this work was to demonstrate how microbiological analyzes (Escherichia. Coli) can contribute to the verification of water security in a rural area. The samples were collected in eleven rural properties in Ilha Solteira - SP. E. coli analyzes were performed using the Colitag method. In the water for human consumption, the presence of E. coli was determined in some rural properties, making it unsuitable for this use according to Consolidation nº 5, of September 28, 2017. In the samples analyzed for human consumption, collected directly from the taps coming from the water tanks, about 48.5% were positive for E.coli. The detection of E.coli in water for human consumption is due to the lack of sanitation and affects water security in the rural area of Ilha Solteira (SP), which requires solutions to eliminate this contamination.

No Brasil, os recursos hídricos chegam a 12% do total de água doce do mundo, o que significa abundância deste recurso considerando apenas o volume. Mesmo abundante, a distribuição é desigual num país de dimensão continental, onde há grande população, há pouca água e onde há baixo índice populacional, grande disponibilidade de água, sendo, ainda que quantidade não é sinônimo de qualidade. No ambiente rural, a principal fonte para obtenção de água é por meio de poços, sendo em sua grande maioria sem outorga, portanto, não se possui conhecimento sobre o estado destas águas quanto a sua qualidade visando os diferentes usos, além das dificuldades que não existem nas zonas urbanas. A falta de acesso à fonte de água potável ainda é uma situação presente na realidade social brasileira, e, particularmente, crítica para parte da população rural, que vive em situação de vulnerabilidade da área, devido as diferenças sociais e a atenção do Estado por meio de políticas públicas. A falta de fiscalização, falta de apoio da gestão e baixíssima cobertura de abastecimento de água em ambientes rurais acarreta assim a falta de segurança hídrica, impactando diretamente na qualidade de vida, e bemestar da população, além alta propagação de doenças. A região de Ilha Solteira (SP) possui uma extensa área rural, em algumas áreas, apesar da proximidade com a área urbana, há falta de saneamento básico e não há a distribuição de água tratada para as famílias, sendo que estas utilizam a água de poço armazenadas em caixas d’água, sem o devido tratamento prévio para seu consumo. O objetivo deste trabalho foi demonstrar como as análises microbiológicas (Escherichia. coli) podem contribuir para verificação da segurança hídrica de uma área rural. As amostras foram coletadas em onze propriedades rurais de Ilha Solteira – SP. As análises de E. coli foram realizadas com o método Colitag. Na água para consumo humano foi determinada a presença de E. coli em algumas propriedades rurais, tornando imprópria para este uso de acordo com Consolidação nº 5, de 28 de setembro de 2017. Nas amostras analisadas para consumo humano, coletadas diretamente das torneiras provenientes das caixas d’água, cerca de 48,5% foram positivas para E.coli. A detecção de E.coli na água para consumo humano deve-se a falta de saneamento e afeta a segurança hídrica na área rural de Ilha Solteira (SP), o que necessita de soluções visando a eliminação desta contaminação.
Keywords: Water and sanitation; Rural settlement; Waterborne diseases; Água potável e saneamento; Assentamento rural; Doenças de veiculação hídrica